'Haven of safety' and 'secure base': a qualitative inquiry into factors affecting child attachment security in Nairobi, Kenya. Issue 4 (1st October 2016) - Polkovnikova-Wamoto, Anastasia; Mathai, Muthoni; Vander Stoep, Ann; Kumar, Manasi
ABSTRACT: Secure attachment in childhood and adolescence protects children from engagement in high-risk behaviors and development of mental health problems over the life span. Poverty has been shown to create impoverishment in certain aspects of caregiving and correspondingly to compromise development of secure attachment in children. Nineteen children 8–14 years old from two schools in a middle-income area and an urban informal settlement area of Nairobi were interviewed using an adapted Child Attachment Interview (CAI) protocol. CAI was developed to provide a glimpse into the 'meta-theories' children have about themselves, parents, parenting, and their attachment ties with parents and extended family members. Narratives obtained with the CAI were analyzed using thematic analysis. Both Bowlby's idea of 'secure base' and Bronfrenbrenner's 'ecological niche' are used as reference points to situate child attachment and parenting practices in the larger Kenyan context. We found that with slight linguistic alterations CAI can be used to assess attachment security of Kenyan children in this particular age range. We also found that the narration ability in both groups of children was generally good such that formal coding was possible despite cultural differences. Our analysis suggested differences in narrative quality across the children from middle class and lower socioeconomic class schools on specific themes such as sensitivity of parenting (main aspects of sensitivity were associated with disciplinary methods and child's access to education), birth order, parental emotional availability, and severity of interparental conflicts and child's level of exposure . The paper puts in context a few cultural practices such as greater household responsibility accorded to the eldest child and stern to harsh disciplinary methods adopted by parents in the Kenyan setting.